2021
DOI: 10.1037/cfp0000174
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning to parenthood during the pandemic: COVID-19 related stressors and first-time expectant mothers’ mental health.

Abstract: The transition to parenthood represents a major life event for expectant parents, influencing personal and relational well-being. Unfortunately, the global coronavirus disease 2019 (COVID-19) pandemic may undermine first-time expectant mothers' emotional health as elevated rates of depression, stress, and anxiety have been noted (Rajkumar, 2020). Thus, the current study was conducted to (a) describe the impact of the COVID-19 pandemic on first-time expectant mothers' pregnancy, prenatal care, internal/ dyadic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 32 publications
1
21
0
3
Order By: Relevance
“…Altered appointments also reduced birth satisfaction [49] and maternal perception of quality of care [37] . Moreover, approximately 70% of mothers who changed their birth plan due to COVID-19-related reasons reported experiencing some level of distress [64] .…”
Section: Resultsmentioning
confidence: 99%
“…Altered appointments also reduced birth satisfaction [49] and maternal perception of quality of care [37] . Moreover, approximately 70% of mothers who changed their birth plan due to COVID-19-related reasons reported experiencing some level of distress [64] .…”
Section: Resultsmentioning
confidence: 99%
“…Stress was also particularly salient for new mothers who were managing their pregnancies or recent births during COVID-19. In a small-scale study of first-time expectant mothers who were in a relationship with their child’s father, experiencing COVID-19-related stressors such as alcohol use and intimate partner violence (IPV) negatively impacted their pregnancy experiences ( McMillan et al, 2021 ). Namely, these stressors exacerbated negative effects on mental health, relationship conflict, and stress related to prenatal care for these first-time mothers ( McMillan et al, 2021 ).…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 99%
“…IPV calls to police stations across the U.S. initially rose by as much as 27% ( Boserup et al, 2020 ) during the pandemic. Further, a small sample of expectant mothers indicated that verbal conflict with their romantic partners increased by over one-third and physical IPV rose 25% during COVID-19’s early stages ( McMillan et al, 2021 ). External stressors such as widespread lockdown restrictions, increased financial strain, lack of alternative housing, and closure of schools and childcare prevented many individuals experiencing IPV from leaving or seeking help (e.g., Evans et al, 2020 ).…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that working part-time during the pandemic provided some of our participants with an essential mix of couple time and economic/insurance benefit. In support of this assertion, a recent study that considered couple functioning among first time mothers during the pandemic also demonstrated that additional couple time in the face of health challenges has a protective function [ 31 ]. However, this additional couple time and greater ability to fulfill familial responsibilities may come with a cost in terms of higher risk of intimate partner violence victimization; IPV victimization may spike when interpersonal expectations are raised but not fulfilled to the perpetrators’ satisfaction.…”
Section: Discussionmentioning
confidence: 96%